2018
DOI: 10.1111/apt.15034
|View full text |Cite
|
Sign up to set email alerts
|

Loss of tolerance to glycoprotein 2 isoforms 1 and 4 is associated with Crohn’s disease of the pouch

Abstract: Summary Background Zymogen granule glycoprotein 2 (GP2) is a major autoantigen of Crohn's disease‐specific pancreatic autoantibodies. Aim To test a link between loss of tolerance to isoforms of GP2 and pouch disorders in a cross‐sectional study in ulcerative colitis patients with ileal pouch‐anal anastomosis (IPAA). Methods Serum samples of 117 consecutive ulcerative colitis patients after IPAA were tested for presence of Anti‐GP2 isoforms 1 (GP21) & 4 (GP24) IgG and IgA as well as anti‐Saccaromyces cervisiae … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Remarkably, GP2 autoAb occurrence could be linked with de novo CD in patients suffering from severe UC with pouchitis after colectomy and ileal pouch anal anastomosis (IPAA) [79,80]. This underscores a close link of the occurrence of GP2 autoAbs with the change of microbiota within the pathophysiology of CD-like symptoms in a formerly UC-driven inflammatory environment.…”
Section: Identification Of Autoantigenic Targets In CDmentioning
confidence: 86%
“…Remarkably, GP2 autoAb occurrence could be linked with de novo CD in patients suffering from severe UC with pouchitis after colectomy and ileal pouch anal anastomosis (IPAA) [79,80]. This underscores a close link of the occurrence of GP2 autoAbs with the change of microbiota within the pathophysiology of CD-like symptoms in a formerly UC-driven inflammatory environment.…”
Section: Identification Of Autoantigenic Targets In CDmentioning
confidence: 86%
“…In regard to localization of the disease, ileum [30,31,40] and ileocolon [32,36,39] were most frequently associated with PAB positivity, followed by perianal disease [13,32,36]. Interestingly, an association between the presence of PABs and pouchitis has also been proposed [43], offering a possible explanation of the role of PABs in the pathogenic process of IBD. Another feature of CD frequently associated with PABs in the literature is disease onset at early age [11,31,32,42].…”
Section: Discussionmentioning
confidence: 96%
“…Although the literature agrees in reporting a low (maximum 40%) prevalence of PAB in CD patients (2, 5-19, 30-32, 36-40), there is a great heterogeneity as regards the correlation with clinical features. If we consider the disease behavior, PAB have been reported to be associated with strictures (2,32,36,41,42). However, some authors have also reported an association with penetrating CD (13,40) and even a negative association with stricturing behavior (8).…”
Section: Discussionmentioning
confidence: 99%